Assessment an Areal Rainfall Technique with Digital Elevation Model Data in Tapi Basin - แต้สมบัติ วิษุวัฒก์ (Srinakharinwirot University Engineering Journal, 2018)
This study aims to compare the areal daily rainfall interpolation derived from ground measurement rainfall by applying 3 techniques of areal interpolation: Co-Kriging, Thin plate spline, and Thiessen polygon. All the techniques were used with SRTM-DEM numerical topographic information of NASA whose horizontal resolution is 90 meters by using daily rainfall data from 12 rainfall stations in Tapi Basin and 8 adjoining stations. This study focused on rainfall data in November 2010, March2011, November2011, and January2012 by testing the accuracy of the interpolation using ME, MAE and RMSE. The result shows that in southern part, whose topography is plain area with few mountains, ME from all methods were negative which means that the interpolation was over-estimated. It was also found that the best ME and RMSE came from Thin plate spline technique, following by Co-Kriging and Thiessen Polygon, respectively. The Thin plate spline is suitable areal rainfall interpolation in Tapi Basin.